Finite Element Simulation of Power Weeder Machine Frame - Angger Bagus Prasetiyo; Kartinasari Ayuhikmatin Sekarjati (Faculty of Engineering and Technology, Sampoerna University, 2022)
One of the agricultural technologies that have evolved recently is the weeding machine. This device was developed to aid farmers in the weed-control procedure. The engine frame is one of the primary elements of the weed wacker. The most crucial component of agricultural equipment is the frame or chassis since it serves as the foundation for mounting other parts. To examine the stress and strength of the frame, this study models the frame of a power weeder machine utilizing finite element analysis using the SolidWorks 2022 program. A total load of 120 N is applied to the AISI 316L used for the frame. The analysis's findings indicate that the maximum von Mises stress value is about 2.51 107N/m2, the greatest deformation is 0.556 mm, and the safety factor is 6.8. With AISI 316L material, the frame design of the power weeder machine in this study is safe to endure up to 140 N.